Diagnostic procedures in ophthalmology - Nema, H. V.; Nema, Nitin (Jaypee Brothers Medical Publishers (P) LTD, 2014)
This third edition presents ophthalmologists and trainees with the most recent developments and research in ophthalmic diagnostic procedures. Beginning with discussion of assessment of visual acuity, each of the following chapters describe diagnostic investigations for numerous ocular disorders, covering both routine and advanced procedures. Existing chapters from previous editions have been fully revised and many new sections added, including imaging in glaucoma, spectrum domain OCT, Pentacam, IOL power calculations, as well as diagnostic modalities of intraocular malignancies, ptosis evaluation, and ocular motor nerve palsies. Neuro-ophthalmic disorders are also covered in depth, with discussion on electrophysiological tests for visual function assessment, and pupil and ocular nerve palsies.